Resin composition, dielectric substrate, and microstrip antenna including the dielectric substrate

The use of surface-treated calcium and magnesium titanate particles with silane compounds in a resin composition addresses the low dielectric tangent issue, resulting in a high-performance dielectric substrate for miniaturized communication devices and antennas.

JP2025070403APending Publication Date: 2025-05-02SUMITOMO BAKELITE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023180698
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing dielectric substrates exhibit low dielectric tangent, particularly in high frequency bands, which hinders the development of high-performance antennas for communication devices.

Method used

A resin composition incorporating surface-treated calcium titanate and magnesium titanate particles with silane compounds, combined with a thermosetting resin and active ester curing agents, to achieve a high dielectric constant and low dielectric tangent.

Benefits of technology

The composition results in a dielectric substrate with improved mechanical strength and reduced dielectric loss, enabling higher frequencies and miniaturization of communication devices, suitable for microstrip antennas and electromagnetic wave absorbers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070403000015
    Figure 2025070403000015
  • Figure 2025070403000016
    Figure 2025070403000016
  • Figure 2025070403000001
    Figure 2025070403000001
Patent Text Reader

Abstract

To provide a resin composition which yields a dielectric substrate having sufficiently high dielectric constant and low dielectric loss tangent, a dielectric substrate composed of the resin composition, and a microstrip antenna including the dielectric substrate.SOLUTION: A resin composition of the present invention contains at least one selected from calcium titanate particles and magnesium titanate particles, subjected to surface treatment with a silane compound.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a dielectric substrate, and a microstrip antenna including the dielectric substrate. [Background technology]

[0002] In recent years, wireless communication has become faster, and there is a demand for higher performance and smaller communication devices. Furthermore, the capacity of wireless communication has increased dramatically in recent years, and the frequency of transmission signals is rapidly becoming wider and higher. As a result, the frequency band used by communication devices is no longer compatible with the microwave band that has been used traditionally, and is expanding to the millimeter wave band. Against this background, there is a strong demand for higher performance antennas installed in communication devices.

[0003] Communication devices can be made even smaller if the dielectric constant of the antenna material (dielectric substrate) built into the device is increased. Also, if the dielectric tangent of the dielectric substrate is reduced, loss is reduced, which is advantageous for higher frequencies. Therefore, if a dielectric substrate with a high dielectric constant and small dielectric tangent can be used, it is possible to increase frequencies, shorten the circuit, and miniaturize the communication device.

[0004] Patent Document 1 discloses an antenna having a circuit board that is a laminate of a dielectric substrate that is a composite material containing a fluororesin and a glass cloth, and an antenna whose surface in contact with the fluororesin has a two-dimensional roughness Ra of less than 0.2 μm. The document describes the dielectric constant and dielectric loss tangent of the circuit board measured at 1 GHz.

[0005] Patent Document 2 discloses a resin composition that contains a siloxane-modified polyamideimide resin, a high dielectric constant filler, and an epoxy resin, and has a relative dielectric constant of a cured product of 15 or more at 25° C. and 1 MHz. The examples in this document describe the use of barium titanate as the high dielectric constant filler.

[0006] Patent Document 3 discloses a resin composition containing an epoxy resin, a dielectric powder, a nonionic surfactant, and an active ester curing agent. The document states that the resin composition can be used as a high dielectric constant insulating material for electronic components used in high frequency regions and as a high dielectric constant insulating material for fingerprint sensors. The examples of the document describe an example in which barium titanate is used as the dielectric powder.

[0007] Patent Document 4 discloses a molding resin composition that contains an epoxy resin, a curing agent such as an active ester curing agent, and an inorganic filler containing calcium titanate particles and strontium titanate particles in a predetermined amount, and is used to seal electronic components in high-frequency devices. The document also describes that the molding resin composition may further contain a silane coupling agent. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2018-41998 A [Patent Document 2] JP 2004-315653 A [Patent Document 3] JP 2020-105523 A [Patent Document 4] Patent No. 6870778 Summary of the Invention [Problem to be solved by the invention]

[0009] However, the molded articles such as dielectric substrates described in Patent Documents 1 to 4 have problems with dielectric properties such as low dielectric tangent, and these problems are particularly noticeable in the high frequency band. [Means for solving the problem]

[0010] The present inventors have found that a dielectric substrate having excellent dielectric properties can be obtained by including a specific high dielectric constant filler that has been surface-treated with a silane compound, and have completed the present invention.

[0011] That is, the present invention can be shown as follows. [1] A resin composition comprising at least one selected from calcium titanate particles and magnesium titanate particles, the particles being surface-treated with a silane compound. [2] The resin composition according to [1], wherein the silane compound is a silane coupling agent. [3] The resin composition according to [2], wherein the silane coupling agent is a phenylaminosilane or a vinylsilane. [4] The resin composition according to any one of [1] to [3], further comprising a thermosetting resin. [5] further comprising a hardener; The resin composition according to any one of [1] to [4], wherein the curing agent includes an active ester curing agent. [6] The resin composition according to any one of [1] to [5], further comprising a curing catalyst. [7] The flexural modulus of the cured product of the resin composition at 260°C is 300 N / mm 2 The resin composition according to any one of [1] to [6] below. [8] The resin composition according to any one of [1] to [7], which is used as a material for forming a microstrip antenna. [9] The resin composition according to any one of [1] to [7], which is used as a material for forming a dielectric waveguide.

[10] The resin composition according to any one of [1] to [7], which is used as a material for forming an electromagnetic wave absorber.

[11] A dielectric substrate obtained by curing the resin composition according to any one of [1] to [7].

[12] A dielectric substrate according to

[11] , a radiating conductor plate provided on one surface of the dielectric substrate; a ground conductor plate provided on the other surface of the dielectric substrate; A microstrip antenna comprising:

[13] A dielectric substrate, a radiating conductor plate provided on one surface of the dielectric substrate; a ground conductor plate provided on the other surface of the dielectric substrate; a high dielectric material disposed opposite the radiation conductor plate; A microstrip antenna comprising: A microstrip antenna, wherein the high dielectric constant material is a dielectric substrate as described in

[11] . Effect of the Invention

[0012] According to the present invention, it is possible to provide a resin composition which can give a dielectric substrate having a high dielectric constant and a low dielectric tangent, a dielectric substrate made of the resin composition, and a microstrip antenna including the dielectric substrate. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a top perspective view showing the microstrip antenna of the present embodiment. [Diagram 2] 10 is a cross-sectional view showing another aspect of the microstrip antenna of the present embodiment. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, the embodiments of the present invention will be described with reference to the drawings. In all drawings, the same components are denoted by the same reference numerals, and the description will be omitted as appropriate. For example, "1 to 10" means "1 or more" to "10 or less" unless otherwise specified.

[0015] The resin composition of the present embodiment contains a high dielectric constant filler, The high dielectric constant filler contains at least one selected from calcium titanate particles (a1) surface-treated with a silane compound and magnesium titanate particles (a2) surface-treated with a silane compound. According to the resin composition of this embodiment, a dielectric substrate having a high dielectric constant, a low dielectric tangent, and excellent mechanical strength such as bending strength and bending modulus can be obtained, and further, a microstrip antenna including the dielectric substrate can be provided.

[0016] [Calcium titanate particles surface-treated with a silane compound (a1)] In this embodiment, the calcium titanate particles (a1) surface-treated with a silane compound (hereinafter also referred to as surface-treated calcium titanate particles (a1)) may be calcium titanate particles in which at least a portion of the surface is surface-treated with a silane compound, and it is preferable that the entire surface of the particles is surface-treated.

[0017] The shape of the surface-treated calcium titanate particles (a1) may be granular, amorphous, flaky, etc., and these shapes of the surface-treated calcium titanate particles (a1) may be used in any ratio. In this embodiment, granular shapes are preferred, and fine particles or spherical particles are more preferred.

[0018] From the viewpoint of the effects of the present invention, the average particle size of the surface-treated calcium titanate particles (a1) is preferably 0.1 μm or more and 50 μm or less, more preferably 0.3 μm or more and 20 μm or less, and further preferably 0.5 μm or more and 10 μm or less.

[0019] In this embodiment, the silane compound used for the surface treatment can be a known silane compound within the scope of the effect of the present invention. The silane compound is preferably a silane coupling agent. It is considered that by previously surface treating calcium titanate particles with a silane coupling agent, functional groups such as hydroxyl groups on the calcium titanate particle surface react with the silane coupling agent, thereby reducing the dielectric tangent.

[0020] Examples of the silane coupling agent include epoxy silane, mercapto silane, amino silane, ureido silane, vinyl silane, and methacryl silane. Examples of epoxy silanes include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and γ-glycidylpropyltrimethoxysilane. An example of the mercaptosilane is 3-mercaptopropyltrimethoxysilane.

[0021] Examples of aminosilanes include phenylaminosilanes such as bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldiethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane.

[0022] An example of the ureidosilane is 3-ureidopropyltriethoxysilane. Examples of vinyl silanes include vinyl tris(β-methoxyethoxy) silane, vinyl triethoxy silane, and vinyl trimethoxy silane. Examples of methacrylsilane include γ-(methacryloxypropyl)trimethoxysilane, γ-(methacryloxypropyl)methyldimethoxysilane, and γ-(methacryloxypropyl)methyldiethoxysilane.

[0023] From the viewpoint of the effects of the present invention, the silane coupling agent is preferably phenylaminosilane or vinylsilane.

[0024] The surface-treated calcium titanate particles (a1) of this embodiment can be prepared by surface-treating calcium titanate particles with a silane compound.

[0025] Specifically, 100 parts by mass of calcium titanate particles are mixed with 0.1 to 10 parts by mass of a silane compound and, if necessary, 0.0001 to 0.001 parts by mass of silicone oil, and then heated at 100 to 140° C. for about 6 to 10 hours to obtain surface-treated calcium titanate particles (a1). Furthermore, the particles are sieved to obtain single particles only.

[0026] [Magnesium titanate particles surface-treated with a silane compound (a2)] In this embodiment, the shape of the magnesium titanate particles (a2) surface-treated with a silane compound (hereinafter also referred to as surface-treated magnesium titanate particles (a2)) may be granular, irregular, flaky, etc., and surface-treated magnesium titanate particles (a2) of these shapes may be used in any ratio. In this embodiment, granular shapes are preferred, and fine particles or spherical particles are more preferred.

[0027] From the viewpoint of the effects of the present invention, the average particle size of the surface-treated magnesium titanate particles (a2) is preferably 0.1 μm or more and 50 μm or less, more preferably 0.3 μm or more and 20 μm or less, and further preferably 0.5 μm or more and 10 μm or less.

[0028] In this embodiment, the silane compound used for the surface treatment may be a known silane compound within the scope of the effects of the present invention. The silane compound is preferably a silane coupling agent, and may be the same as that of the surface-treated calcium titanate particles (a1). The silane compound of the surface-treated calcium titanate particles (a1) and the silane compound of the surface-treated magnesium titanate particles (a2) may be the same or different.

[0029] It is believed that by previously treating the surface of magnesium titanate particles with a silane coupling agent, functional groups such as hydroxyl groups on the surface of the magnesium titanate particles react with the silane coupling agent, thereby reducing the dielectric tangent.

[0030] The surface-treated magnesium titanate particles (a2) of this embodiment can be prepared by surface-treating magnesium titanate particles with a silane compound in the same manner as the surface-treated calcium titanate particles (a1).

[0031] The resin composition of the present embodiment may contain a dielectric filler consisting of at least one selected from surface-treated calcium titanate particles (a1) and surface-treated magnesium titanate particles (a2) in an amount of preferably 30% by mass to 95% by mass, more preferably 40% by mass to 90% by mass, and even more preferably 50% by mass to 85% by mass, based on the entire resin composition. When the amount of the high dielectric filler added is within the above range, the resulting cured product has a high dielectric constant and a low dielectric tangent, and is excellent in the production of molded products.

[0032] When the high dielectric constant filler of the present embodiment contains both surface-treated calcium titanate particles (a1) and surface-treated magnesium titanate particles (a2), the filler preferably contains particles (a1) in an amount of 20% by mass or more and 90% by mass or less, more preferably 30% by mass or more and 85% by mass or less, and even more preferably 40% by mass or more and 80% by mass or less, and the filler preferably contains particles (a2) in an amount of 10% by mass or more and 80% by mass or less, more preferably 15% by mass or more and 70% by mass or less, and even more preferably 20% by mass or more and 60% by mass or less, relative to 100% by mass of the total of particles (a1) and particles (a2).

[0033] [Other high dielectric constant fillers] The resin composition of the present embodiment may contain other high dielectric constant fillers in addition to the surface-treated calcium titanate particles (a1) and the surface-treated magnesium titanate particles (a2).

[0034] Other high dielectric constant fillers include barium titanate, calcium titanate, strontium titanate, magnesium titanate, magnesium zirconate, strontium zirconate, bismuth titanate, zirconium titanate, zinc titanate, barium zirconate, calcium zirconate titanate, lead zirconate titanate, barium magnesium niobate, calcium zirconate, and the like, and one or more types selected from these can be used. The other shapes of the high dielectric constant filler include granular, irregular, and flaky shapes, and the high dielectric constant fillers in these shapes can be used in any ratio.

[0035] The amount of the other high dielectric constant filler blended is preferably in the range of 10% by mass to 80% by mass, more preferably 20% by mass to 70% by mass, and even more preferably 30% by mass to 60% by mass, based on the entire resin composition.

[0036] [Thermosetting resin] The resin composition of the present embodiment may further contain a thermosetting resin. The thermosetting resin may be one or more selected from cyanate resin, epoxy resin, resin having two or more radically polymerizable carbon-carbon double bonds in one molecule, and maleimide resin. Among these, it is particularly preferable to include an epoxy resin from the viewpoint of improving the effects of the present invention and the adhesiveness of the thermal conductive paste. As the epoxy resin, any monomer, oligomer, or polymer having two or more epoxy groups in one molecule can be used, and the molecular weight and molecular structure thereof are not limited.

[0037] Examples of the epoxy resin include biphenyl type epoxy resins; bisphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, and tetramethylbisphenol F type epoxy resins; stilbene type epoxy resins; novolac type epoxy resins such as phenol novolac type epoxy resins and cresol novolac type epoxy resins; polyfunctional epoxy resins such as trisphenol type epoxy resins exemplified by triphenol methane type epoxy resins and alkyl-modified triphenol methane type epoxy resins; phenol aralkyl type epoxy resins having a phenylene skeleton, naphthol aralkyl type epoxy resins having a phenylene skeleton, and the like. the epoxy resins include one or more selected from the group consisting of phenol aralkyl-type epoxy resins such as phenol aralkyl-type epoxy resins having a biphenylene skeleton, and naphthol aralkyl-type epoxy resins having a biphenylene skeleton; naphthol-type epoxy resins such as dihydroxynaphthalene-type epoxy resins and epoxy resins obtained by glycidyl etherifying a dimer of dihydroxynaphthalene; triazine nucleus-containing epoxy resins such as triglycidyl isocyanurate and monoallyl diglycidyl isocyanurate; and bridged cyclic hydrocarbon compound-modified phenol-type epoxy resins such as dicyclopentadiene-modified phenol-type epoxy resins.

[0038] Of these, novolac type epoxy resins, polyfunctional epoxy resins, and phenol aralkyl type epoxy resins can be preferably used. From the same viewpoint, the epoxy resin preferably contains one or more selected from the group consisting of orthocresol novolac type epoxy resins, phenol aralkyl type epoxy resins having a biphenylene skeleton, and triphenylmethane type epoxy resins, and more preferably contains one or more selected from the group consisting of orthocresol novolac type epoxy resins and phenol aralkyl type epoxy resins having a biphenylene skeleton.

[0039] From the viewpoint of the effects of the present invention, the thermosetting resin such as an epoxy resin may be contained in an amount of preferably 2% by mass or more, more preferably 3% by mass or more, and even more preferably 4% by mass or more, based on the entire resin composition. The epoxy resin may be contained in an amount of typically 15% by mass or less, more preferably 12% by mass or less, and even more preferably 10% by mass or less.

[0040] [Hardening agent] The resin composition of the present embodiment may further contain a curing agent. The hardener includes an active ester hardener and may further include other hardeners.

[0041] (Active ester hardener) As the active ester curing agent, a compound having one or more active ester groups in one molecule can be used. Among them, as the active ester curing agent, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferred.

[0042] Preferred specific examples of the active ester curing agent include an active ester curing agent containing a dicyclopentadiene-type diphenol structure, an active ester curing agent containing a naphthalene structure, an active ester curing agent containing an acetylated product of phenol novolac, and an active ester curing agent containing a benzoylated product of phenol novolac, and at least one of them can be included. Among them, an active ester curing agent containing a naphthalene structure and an active ester curing agent containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene. In this embodiment, the active ester curing agent may be, for example, a resin having a structure represented by the following general formula (1).

[0043] [ka] In general formula (1), "B" is a structure represented by general formula (B).

[0044] [ka]

[0045] In general formula (B), Ar is a substituted or unsubstituted arylene group. Examples of the substituent of the substituted arylene group include an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a phenyl group, and an aralkyl group.

[0046] Y is a single bond, a substituted or unsubstituted linear alkylene group having 1 to 6 carbon atoms, a substituted or unsubstituted cyclic alkylene group having 3 to 6 carbon atoms, a substituted or unsubstituted divalent aromatic hydrocarbon group, an ether bond, a carbonyl group, a carbonyloxy group, a sulfide group, or a sulfone group. Examples of the substituent of the above group include an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a phenyl group, and an aralkyl group.

[0047] Preferred examples of Y include a single bond, a methylene group, -CH(CH3)2-, an ether bond, an optionally substituted cycloalkylene group, and an optionally substituted 9,9-fluorenylene group. n is an integer of 0 to 4, and is preferably 0 or 1. Specifically, B is a structure represented by the following general formula (B1) or the following general formula (B2).

[0048] [ka]

[0049] In the above general formula (B1) and the above general formula (B2), Ar and Y have the same meanings as in the general formula (B). A is a substituted or unsubstituted arylene group linked via an aliphatic cyclic hydrocarbon group; Ar' is a substituted or unsubstituted aryl group; k is the average value of the repeating units and is in the range of 0.25 to 3.5. The resin composition of the present embodiment contains a specific active ester curing agent, and thus the resulting cured product can have excellent dielectric properties and an excellent low dielectric tangent.

[0050] The active ester curing agent used in the resin composition of this embodiment has an active ester group represented by formula (B). In the curing reaction between the epoxy resin, which is a thermosetting resin, and the active ester curing agent, the active ester group of the active ester curing agent reacts with the epoxy group of the epoxy resin to generate a secondary hydroxyl group. This secondary hydroxyl group is blocked by the ester residue of the active ester curing agent. Therefore, the dielectric tangent of the cured product is reduced. In one embodiment, the structure represented by the above formula (B) is preferably at least one selected from the following formulae (B-1) to (B-6).

[0051] [ka]

[0052] In formulas (B-1) to (B-6), R 1 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a phenyl group, or an aralkyl group,

[0053] R 2 each independently represents an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a phenyl group; X represents a linear alkylene group having 2 to 6 carbon atoms, an ether bond, a carbonyl group, a carbonyloxy group, a sulfide group, or a sulfone group; n is an integer of 0 to 4, and p is an integer of 1 to 4.

[0054] Since the structures represented by the above formulas (B-1) to (B-6) are all highly oriented structures, when an active ester curing agent containing such structures is used, the cured product of the resulting resin composition has a low dielectric tangent and excellent adhesion to metals, and therefore can be suitably used as a semiconductor encapsulation material.

[0055] Among them, from the viewpoint of low dielectric tangent, active ester curing agents having a structure represented by formula (B-2), formula (B-3) or formula (B-5) are preferred, and active ester curing agents having a structure in which n in formula (B-2) is 0, a structure in which X in formula (B-3) is an ether bond, or a structure in which two carbonyloxy groups are at the 4,4'-position in formula (B-5) are more preferred. 1 are preferably all hydrogen atoms.

[0056] In formula (1), "Ar'" is an aryl group, and may be, for example, a phenyl group, an o-tolyl group, an m-tolyl group, a p-tolyl group, a 3,5-xylyl group, an o-biphenyl group, an m-biphenyl group, a p-biphenyl group, a 2-benzylphenyl group, a 4-benzylphenyl group, a 4-(α-cumyl)phenyl group, a 1-naphthyl group, a 2-naphthyl group, etc. Among these, a 1-naphthyl group or a 2-naphthyl group is preferable, since a cured product having a particularly low dielectric tangent can be obtained.

[0057] In this embodiment, "A" in the active ester curing agent represented by formula (1) is a substituted or unsubstituted arylene group linked via an aliphatic cyclic hydrocarbon group. Examples of such arylene groups include a structure obtained by a polyaddition reaction between an unsaturated aliphatic cyclic hydrocarbon compound containing two double bonds in one molecule and a phenolic compound.

[0058] Examples of the unsaturated aliphatic cyclic hydrocarbon compound containing two double bonds in one molecule include dicyclopentadiene, cyclopentadiene polymers, tetrahydroindene, 4-vinylcyclohexene, 5-vinyl-2-norbornene, and limonene, which may be used alone or in combination of two or more. Among these, dicyclopentadiene is preferred because it can provide a cured product with excellent heat resistance. Since dicyclopentadiene is contained in petroleum fractions, industrial dicyclopentadiene may contain cyclopentadiene polymers and other aliphatic or aromatic diene compounds as impurities, but considering performance such as heat resistance, curability, and moldability, it is desirable to use a product with a purity of 90% by mass or more of dicyclopentadiene.

[0059] On the other hand, the phenolic compound may be, for example, phenol, cresol, xylenol, ethylphenol, isopropylphenol, butylphenol, octylphenol, nonylphenol, vinylphenol, isopropenylphenol, allylphenol, phenylphenol, benzylphenol, chlorophenol, bromophenol, 1-naphthol, 2-naphthol, 1,4-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, etc., each of which may be used alone or in combination of two or more kinds. Among these, phenol is preferred because it is an active ester curing agent with high curing property and excellent dielectric properties in the cured product.

[0060] In a preferred embodiment, "A" in the active ester curing agent represented by formula (1) has a structure represented by formula (A). A resin composition containing an active ester curing agent in which "A" in formula (1) has the following structure has a cured product with a low dielectric tangent and excellent adhesion to insert products.

[0061] [ka]

[0062] In formula (A), R 3 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a phenyl group, or an aralkyl group, l is 0 or 1, and m is an integer of 1 or more.

[0063] Among the active ester curing agents represented by formula (1), more preferred are resins represented by the following formulas (1-1), (1-2) and (1-3), and particularly preferred is the resin represented by the following formula (1-3).

[0064] [ka]

[0065] In formula (1-1), R 1 and R 3 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a phenyl group, or an aralkyl group; Z represents a phenyl group, a naphthyl group, or a phenyl group or naphthyl group having 1 to 3 alkyl groups having 1 to 4 carbon atoms on the aromatic nucleus; l is 0 or 1; and k is the average of the repeating units and is 0.25 to 3.5.

[0066] [ka]

[0067] In formula (1-2), R 1 and R 3 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a phenyl group, or an aralkyl group; Z represents a phenyl group, a naphthyl group, or a phenyl group or naphthyl group having 1 to 3 alkyl groups having 1 to 4 carbon atoms on the aromatic nucleus; l is 0 or 1; and k is the average of the repeating units and is 0.25 to 3.5.

[0068] [ka]

[0069] In formula (1-3), R 1 and R 3 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a phenyl group, or an aralkyl group; Z represents a phenyl group, a naphthyl group, or a phenyl group or naphthyl group having 1 to 3 alkyl groups having 1 to 4 carbon atoms on the aromatic nucleus; l is 0 or 1; and k is the average of the repeating units and is 0.25 to 3.5.

[0070] The active ester curing agent used in the present embodiment can be produced by a known method in which a phenolic compound (a) having a structure in which a plurality of aryl groups each having a phenolic hydroxyl group are bonded via an aliphatic cyclic hydrocarbon group, an aromatic nucleus-containing dicarboxylic acid or its halide (b), and an aromatic monohydroxy compound (c) are reacted.

[0071] The reaction ratio of the phenolic compound (a), aromatic nucleus-containing dicarboxylic acid or its halide (b), and aromatic monohydroxy compound (c) can be appropriately adjusted according to the desired molecular design. Among them, since an active ester curing agent having higher curing properties can be obtained, it is preferable to use each raw material in a ratio such that the phenolic hydroxyl group of the phenolic compound (a) is in the range of 0.25 to 0.90 moles and the hydroxyl group of the aromatic monohydroxy compound (c) is in the range of 0.10 to 0.75 moles per 1 mole of the total of the carboxyl group or acid halide group of the aromatic nucleus-containing dicarboxylic acid or its halide (b), and it is more preferable to use each raw material in a ratio such that the phenolic hydroxyl group of the phenolic compound (a) is in the range of 0.50 to 0.75 moles and the hydroxyl group of the aromatic monohydroxy compound (c) is in the range of 0.25 to 0.50 moles.

[0072] In addition, when the total number of arylcarbonyloxy groups and phenolic hydroxyl groups in the resin structure is taken as the number of functional groups of the resin, the functional group equivalent of the active ester curing agent is preferably in the range of 200 g / eq or more and 230 g / eq or less, and more preferably in the range of 210 g / eq or more and 220 g / eq or less, in order to obtain a cured product with excellent curing properties and low dielectric constant and dielectric dissipation factor.

[0073] In the resin composition of the present embodiment, the amount of active ester curing agent and epoxy resin is preferably such that the epoxy group in the epoxy resin is 0.8 to 1.2 equivalents per equivalent of the total active groups in the active ester curing agent, since this gives a cured product with excellent curing properties and low dielectric tangent. Here, the active groups in the active ester curing agent refer to the arylcarbonyloxy group and phenolic hydroxyl group in the resin structure.

[0074] In the composition of the present embodiment, the active ester curing agent is used in an amount of preferably 0.2 mass % or more and 15 mass % or less, more preferably 0.5 mass % or more and 10 mass % or less, and even more preferably 1.0 mass % or more and 7 mass % or less, based on the entire resin composition. By including the specific active ester curing agent in the above range, the resulting cured product can have better dielectric properties and is even more excellent in low dielectric tangent.

[0075] The resin composition of the present embodiment uses an active ester curing agent in combination with the high dielectric constant filler described above, and thus has a high dielectric constant and a low dielectric loss tangent, and these effects are also excellent in the high frequency band.

[0076] From the viewpoint of the above-mentioned effects, the active ester curing agent can be contained in an amount of preferably 1 part by mass or more and 30 parts by mass or less, more preferably 2 parts by mass or more and 20 parts by mass or less, and even more preferably 3 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of the above-mentioned high dielectric constant filler.

[0077] [Other hardeners] The resin composition of the present embodiment may further contain a curing agent other than the active ester curing agent.

[0078] Examples of the curing agent include amine compounds such as diaminodiphenylmethane, diethylenetriamine, triethylenetetramine, diaminodiphenylsulfone, isophoronediamine, imidazole, BF3-amine complex, and guanidine derivatives; amide compounds such as polyamide resins synthesized from dicyandiamide and a dimer of linoleic acid and ethylenediamine; acid anhydrides such as phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride; phenol novolac resins, cresol novolac resins, and aromatic hydrocarbon formaldehyde resin-modified phenol resins. Examples of polyhydric phenol compounds include polyphenol compounds such as dicyclopentadiene-phenol addition type resins, phenol aralkyl resins, naphthol aralkyl resins, trimethylolmethane resins, tetraphenylolethane resins, naphthol novolak resins, naphthol-phenol co-condensed novolak resins, naphthol-cresol co-condensed novolak resins, biphenyl-modified phenol resins (polyhydric phenol compounds in which phenol nuclei are linked via bismethylene groups), biphenyl-modified naphthol resins (polyhydric naphthol compounds in which phenol nuclei are linked via bismethylene groups), and aminotriazine-modified phenol resins (polyhydric phenol compounds in which phenol nuclei are linked via melamine, benzoguanamine, or the like), and phenol aralkyl resins are preferred.

[0079] When another curing agent is used together with the active ester curing agent, the amount of the other curing agent is preferably 0.5% by mass or more and 20% by mass or less, more preferably 1.0% by mass or more and 15% by mass or less, and even more preferably 2.0% by mass or more and 10% by mass or less, based on the thermosetting resin. By using the curing agent in the amount within the above range, a resin composition having excellent curability can be obtained.

[0080] [Curing catalyst] The resin composition of the present embodiment may further contain a curing catalyst. The curing catalyst may also be called a curing accelerator, etc. The curing catalyst is not particularly limited as long as it accelerates the curing reaction of the thermosetting resin, and any known curing catalyst may be used.

[0081] Specific examples of such compounds include phosphorus atom-containing compounds such as organic phosphines, tetra-substituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, and adducts of phosphonium compounds and silane compounds; imidazoles (imidazole-based curing accelerators) such as 2-methylimidazole and 2-phenylimidazole; and nitrogen atom-containing compounds such as amidines and tertiary amines, exemplified by 1,8-diazabicyclo[5.4.0]undecene-7 and benzyldimethylamine, and quaternary salts of amidines and amines. Only one type of compound may be used, or two or more types may be used.

[0082] Among these, from the viewpoint of improving curability and obtaining a cured product excellent in mechanical strength such as bending strength and bending modulus, it is preferable to contain a phosphorus atom-containing compound, more preferably to contain one having latency such as a tetra-substituted phosphonium compound, a phosphobetaine compound, an adduct of a phosphine compound and a quinone compound, or an adduct of a phosphonium compound and a silane compound, and particularly preferably a tetra-substituted phosphonium compound, an adduct of a phosphine compound and a quinone compound, or an adduct of a phosphonium compound and a silane compound.

[0083] By using a combination of the active ester curing agent (B1) represented by general formula (1) and a latent curing catalyst, it is possible to obtain a cured product that is excellent in moldability and mechanical strength, such as bending strength and bending modulus.

[0084] Examples of the organic phosphines include primary phosphines such as ethylphosphine and phenylphosphine; secondary phosphines such as dimethylphosphine and diphenylphosphine; and tertiary phosphines such as trimethylphosphine, triethylphosphine, tributylphosphine and triphenylphosphine. Examples of the tetra-substituted phosphonium compound include compounds represented by the following general formula (6).

[0085] [ka]

[0086] In general formula (6), P represents a phosphorus atom. R 4 , R 5 , R 6 and R 7 each independently represents an aromatic group or an alkyl group. A represents the anion of an aromatic organic acid having at least one functional group selected from a hydroxyl group, a carboxyl group, and a thiol group on an aromatic ring. AH represents an aromatic organic acid having at least one functional group selected from a hydroxyl group, a carboxyl group, and a thiol group on an aromatic ring. x and y are 1 to 3, z is 0 to 3, and x=y.

[0087] The compound represented by the general formula (6) can be obtained, for example, as follows. First, a tetra-substituted phosphonium halide, an aromatic organic acid, and a base are mixed uniformly in an organic solvent to generate an aromatic organic acid anion in the solution system. Then, water is added to precipitate the compound represented by general formula (6). In the compound represented by general formula (6), R bonded to the phosphorus atom 4 , R 5 , R 6 and R 7is preferably a phenyl group, AH is a compound having a hydroxyl group on an aromatic ring, i.e., a phenol, and A is an anion of the phenol. Examples of the phenol include monocyclic phenols such as phenol, cresol, resorcin, and catechol, condensed polycyclic phenols such as naphthol, dihydroxynaphthalene, and anthraquinol, bisphenols such as bisphenol A, bisphenol F, and bisphenol S, and polycyclic phenols such as phenylphenol and biphenol.

[0088] Examples of the phosphobetaine compound include compounds represented by the following general formula (7).

[0089] [ka]

[0090] In general formula (7), P represents a phosphorus atom. R 8 is an alkyl group having 1 to 3 carbon atoms, R 9 represents a hydroxyl group. f is 0 to 5 and g is 0 to 3.

[0091] The compound represented by the general formula (7) can be obtained, for example, as follows. First, a triaromatic substituted phosphine, which is a tertiary phosphine, is contacted with a diazonium salt to substitute the diazonium group of the diazonium salt for the triaromatic substituted phosphine.

[0092] Examples of the adduct of a phosphine compound and a quinone compound include compounds represented by the following general formula (8).

[0093] [ka]

[0094] In general formula (8), P represents a phosphorus atom. R 10 , R 11 and R 12 represents an alkyl group having 1 to 12 carbon atoms or an aryl group having 6 to 12 carbon atoms, and may be the same or different.

[0095] R 13 , R 14 and R 15 represents a hydrogen atom or a hydrocarbon group having 1 to 12 carbon atoms, and may be the same or different; R 14 and R 15 may be bonded to form a cyclic structure.

[0096] The phosphine compound used in the adduct of the phosphine compound and the quinone compound is preferably, for example, triphenylphosphine, tris(alkylphenyl)phosphine, tris(alkoxyphenyl)phosphine, trinaphthylphosphine, tris(benzyl)phosphine, etc., which is unsubstituted or has a substituent such as an alkyl group or an alkoxy group on the aromatic ring, and examples of the substituent such as the alkyl group or alkoxy group include those having a carbon number of 1 to 6. From the viewpoint of availability, triphenylphosphine is preferred.

[0097] As the quinone compound used in the adduct of the phosphine compound and the quinone compound, benzoquinone and anthraquinones can be mentioned, and among them, p-benzoquinone is preferred from the viewpoint of storage stability.

[0098] The method for producing an adduct of a phosphine compound and a quinone compound is to contact and mix the organic tertiary phosphine and the benzoquinone in a solvent in which both can dissolve, to obtain the adduct. The solvent is preferably a ketone such as acetone or methyl ethyl ketone, which has low solubility in the adduct, but is not limited thereto.

[0099] In the compound represented by the general formula (8), R bonded to the phosphorus atom 10 , R 11 and R12 is a phenyl group, and R 13 , R 14 and R 15 A compound in which is a hydrogen atom, that is, an addition compound of 1,4-benzoquinone and triphenylphosphine, is preferred in terms of decreasing the hot elastic modulus of the cured product of the encapsulating resin composition.

[0100] Examples of the adduct of a phosphonium compound and a silane compound include a compound represented by the following general formula (9).

[0101] [ka]

[0102] In general formula (9), P represents a phosphorus atom, and Si represents a silicon atom.

[0103] R 16 , R 17 , R 18 and R 19 each represents an organic group having an aromatic ring or a heterocycle, or an aliphatic group, and may be the same or different. R 20 is the group Y 2 and Y 3 It is an organic group that bonds to R 21 is the group Y 4 and Y 5 It is an organic group that bonds to

[0104] Y 2 and Y 3 represents a group formed by releasing a proton from a proton-donating group, and a group Y 2 and Y 3 is bonded to a silicon atom to form a chelate structure.

[0105] Y 4 and Y 5 represents a group formed by releasing a proton from a proton-donating group, and a group Y 4and Y 5 is bonded to a silicon atom to form a chelate structure. R 20 , and R 21 may be the same or different, and Y 2 , Y 3 , Y 4 and Y 5 may be the same or different from each other. Z1 is an organic group having an aromatic ring or a heterocyclic ring, or an aliphatic group.

[0106] In the general formula (9), R 16 , R 17 , R 18 and R 19 Examples of the alkyl group include a phenyl group, a methylphenyl group, a methoxyphenyl group, a hydroxyphenyl group, a naphthyl group, a hydroxynaphthyl group, a benzyl group, a methyl group, an ethyl group, an n-butyl group, an n-octyl group, and a cyclohexyl group. Among these, an aromatic group having a substituent such as an alkyl group, an alkoxy group, or a hydroxyl group, such as a phenyl group, a methylphenyl group, a methoxyphenyl group, a hydroxyphenyl group, or a hydroxynaphthyl group, or an unsubstituted aromatic group is more preferable.

[0107] In the general formula (9), R 20 is Y 2 and Y 3 Similarly, R 21 is the group Y 4 and Y 5 It is an organic group that bonds with Y. 2 and Y 3 is a group formed by releasing a proton from a proton-donating group, and a group Y 2 and Y 3 is bonded to a silicon atom to form a chelate structure. 4 and Y 5 is a group formed by releasing a proton from a proton-donating group, and a group Y 4 and Y 5 is bonded to a silicon atom to form a chelate structure. 20and R 21 may be the same or different, and the group Y 2 , Y 3 , Y 4 and Y5 may be the same or different. 2 -R 20 -Y 3 - and Y 4 -R 21 -Y 5 The group represented by - is composed of a group formed by releasing two protons from a proton donor. As the proton donor, an organic acid having at least two carboxyl groups or hydroxyl groups in the molecule is preferable, an aromatic compound having at least two carboxyl groups or hydroxyl groups on adjacent carbons constituting an aromatic ring is more preferable, and an aromatic compound having at least two hydroxyl groups on adjacent carbons constituting an aromatic ring is more preferable. Examples of the proton donor include catechol, pyrogallol, 1,2-dihydro- Examples of the hydroxynaphthalene include xynaphthalene, 2,3-dihydroxynaphthalene, 2,2'-biphenol, 1,1'-bi-2-naphthol, salicylic acid, 1-hydroxy-2-naphthoic acid, 3-hydroxy-2-naphthoic acid, chloranilic acid, tannic acid, 2-hydroxybenzyl alcohol, 1,2-cyclohexanediol, 1,2-propanediol, and glycerin. Of these, catechol, 1,2-dihydroxynaphthalene, and 2,3-dihydroxynaphthalene are more preferred.

[0108] Z in general formula (9) 1 represents an organic group or an aliphatic group having an aromatic ring or a heterocyclic ring, and specific examples thereof include aliphatic hydrocarbon groups such as methyl group, ethyl group, propyl group, butyl group, hexyl group, and octyl group; aromatic hydrocarbon groups such as phenyl group, benzyl group, naphthyl group, and biphenyl group; glycidyloxy groups such as glycidyloxypropyl group, mercaptopropyl group, and aminopropyl group; mercapto group; and reactive substituents such as an alkyl group having an amino group and a vinyl group. Among these, the methyl group, the ethyl group, the phenyl group, the naphthyl group, and the biphenyl group are more preferable in terms of thermal stability.

[0109] A method for producing an adduct of a phosphonium compound and a silane compound is, for example, as follows. In a flask containing methanol, a silane compound such as phenyltrimethoxysilane and a proton donor such as 2,3-dihydroxynaphthalene are dissolved, and then a sodium methoxide-methanol solution is added dropwise at room temperature with stirring. A previously prepared solution of a tetra-substituted phosphonium halide such as tetraphenylphosphonium bromide dissolved in methanol is then added dropwise at room temperature with stirring, causing crystals to precipitate. The precipitated crystals are filtered, washed with water, and vacuum dried to obtain an adduct of the phosphonium compound and the silane compound.

[0110] When a curing catalyst is used, its content is preferably 0.01 to 1 mass %, more preferably 0.02 to 0.8 mass %, based on the total mass of the resin composition. By setting the content within such a numerical range, a sufficient curing acceleration effect can be obtained without excessively impairing other performances.

[0111] [Inorganic filler] The resin composition of the present embodiment may further contain an inorganic filler in addition to the high dielectric constant filler in order to reduce moisture absorption, reduce the linear expansion coefficient, improve thermal conductivity, and improve strength.

[0112] Examples of inorganic fillers include powders such as fused silica, crystalline silica, alumina, calcium silicate, calcium carbonate, potassium titanate, silicon carbide, silicon nitride, aluminum nitride, boron nitride, beryllia, zirconia, zircon, fosterite, steatite, spinel, mullite, and titania, or beads or glass fibers obtained by sphering these. These inorganic fillers may be used alone or in combination of two or more. Among the above inorganic fillers, fused silica is preferred from the viewpoint of reducing the linear expansion coefficient, and alumina is preferred from the viewpoint of high thermal conductivity, and the filler shape is preferably spherical from the viewpoint of fluidity during molding and mold wear resistance.

[0113] The amount of inorganic filler other than the high dielectric constant filler may be preferably 15% by mass or more and 60% by mass or less, more preferably 20% by mass or more and 50% by mass or less, based on the entire resin composition, from the viewpoints of moldability, reduction in thermal expansion, and improvement in strength. If it is within the above range, the thermal expansion reduction and moldability are excellent.

[0114] [Silane coupling agents] The resin composition of the present embodiment may further contain a silane coupling agent. The silane coupling agent is not a silane coupling agent attached to the surface of the surface-treated calcium titanate particles (a1) or the surface-treated magnesium titanate particles (a2), but is added separately. Examples of the silane coupling agent include the silane coupling agents exemplified in the surface-treated calcium titanate particles (a1).

[0115] When a silane coupling agent is used, its content is preferably 0.01 to 1 mass %, more preferably 0.02 to 0.8 mass %, based on the total mass of the resin composition. By setting the content within such a numerical range, adhesion to the substrate is improved.

[0116] [Other ingredients] In addition to the above components, the resin composition of the present embodiment may contain various components such as a release agent, a colorant, a dispersant, and a stress reducing agent, as necessary.

[0117] [Resin composition] The resin composition of the present embodiment can be produced by uniformly mixing the above-mentioned components. The production method includes a method in which a predetermined amount of raw materials is thoroughly mixed using a mixer or the like, then melt-kneaded using a mixing roll, kneader, extruder, or the like, and then cooled and pulverized. The obtained resin composition may be tableted to a size and mass suitable for molding conditions, as necessary.

[0118] The properties of the resin composition of the present embodiment are shown below. The properties can be controlled by appropriately selecting the types and amounts of each component contained in the resin composition, the method for preparing the resin composition, and the like.

[0119] The resin composition of the present embodiment can have a linear expansion coefficient CTE1 at a temperature below the glass transition temperature of a cured product of the resin composition, measured under the following conditions, of 10 ppm / °C or more and 30 ppm / °C or less, preferably 15 ppm / °C or more and 25 ppm / °C or less. By having the linear expansion coefficient (CTE1) within the above range, the stress caused by the difference in the linear expansion coefficient with other antenna materials is further alleviated, warping when used as an antenna material can be reduced, and product reliability is excellent.

[0120] Furthermore, the resin composition of this embodiment can have a linear expansion coefficient CTE2 at a temperature equal to or higher than the glass transition temperature of a cured product of the resin composition, measured under the following conditions, of 40 ppm / ° C. to 80 ppm / ° C., preferably 55 ppm / ° C. to 75 ppm / ° C. This can reduce warping when used as an antenna material, and provides excellent product reliability at high temperatures.

[0121] (Method of measuring linear expansion coefficient) The resin composition is injected and molded using a transfer molding machine at a mold temperature of 175°C, injection pressure of 9.8MPa, and curing time of 180 seconds to obtain a test piece (cured product) with a long side of 15mm, a short side of 4mm, and a thickness of 4mm. The test piece is post-cured at 175°C for 4 hours, and then measured using a thermomechanical analyzer in compression mode under the conditions of a measurement temperature range of 0°C to 320°C and a heating rate of 5°C / min. From the measurement results, the glass transition temperature (Tg) and the average linear expansion coefficient at a temperature below the glass transition temperature are calculated and designated as CTE1, and the average linear expansion coefficient at a temperature equal to or higher than the glass transition temperature is designated as CTE2.

[0122] The resin composition of the present embodiment has a bending strength of 1 N / mm at 260° C. when cured, as measured by the following method. 2 More than 2N / mm 2The upper limit is not particularly limited, but it can be 20 N / mm 2 This provides the cured product with excellent mechanical strength and makes it suitable for use as an antenna material.

[0123] Furthermore, the resin composition of the present embodiment preferably has a flexural modulus at 260° C. of 300 N / mm 2 Less than or equal to 250N / mm 2 Less than 200N / mm 2 The lower limit is not particularly limited, but it can be 50 N / mm 2 As a result, the cured product has excellent mechanical strength and can be suitably used as an antenna material. (Method of measuring bending strength and bending modulus) The resin composition is injected into a transfer molding machine at a mold temperature of 175°C, injection pressure of 9.8 MPa, and curing time of 180 seconds to obtain a molded product of width 10 mm x thickness 4 mm x length 80 mm, which is then post-cured at 175°C for 4 hours to obtain a test piece. The flexural strength and flexural modulus of the test piece at 260°C are measured in accordance with JIS K 6911.

[0124] The cured product obtained from the resin composition of the present embodiment has a high dielectric constant and a low dielectric tangent in the high frequency band, which enables higher frequencies, shorter circuits, and smaller communication devices, etc., and can be suitably used as a material for forming a microstrip antenna, a material for forming a dielectric waveguide, and further a material for forming an electromagnetic wave absorber, etc.

[0125] <Microstrip antenna> 1, the microstrip antenna 10 of this embodiment includes a dielectric substrate 12 formed by curing the above-mentioned resin composition, a radiating conductor plate (radiating element) 14 provided on one surface of the dielectric substrate 12, and a ground conductor plate 16 provided on the other surface of the dielectric substrate 12. At least a portion of the radiating conductor plate 12 is embedded in the dielectric substrate 12. The shape of the radiating conductor plate may be rectangular or circular, and in this embodiment, a rectangular radiating conductor plate 14 will be used as an example.

[0126] The radiation conductor plate 14 includes any one of a metal material, an alloy of a metal material, a hardened metal paste, and a conductive polymer. The metal material includes copper, silver, palladium, gold, platinum, aluminum, chromium, nickel, cadmium-lead, selenium, manganese, tin, vanadium, lithium, cobalt, and titanium. The alloy includes a plurality of metal materials. The metal paste agent includes a mixture of powder of a metal material with an organic solvent and a binder. The binder includes an epoxy resin, a polyester resin, a polyimide resin, a polyamide-imide resin, and a polyetherimide resin. The conductive polymer includes a polythiophene-based polymer, a polyacetylene-based polymer, a polyaniline-based polymer, a polypyrrole-based polymer, and the like.

[0127] 1, the microstrip antenna 10 of this embodiment has a radiating conductor plate 14 with a length L and a width W, and resonates at a frequency where L is an integer multiple of 1 / 2 the wavelength. When using a dielectric substrate 12 with a high dielectric constant as in this embodiment, the thickness h of the dielectric substrate 12 and the width W of the radiating conductor plate 14 are designed to be sufficiently small compared to the wavelength.

[0128] The ground conductor plate 16 is a thin plate made of a highly conductive metal such as copper, silver, gold, etc. Its thickness is sufficiently thin compared to the central operating frequency of the antenna device, and may be approximately 1 / 50 to 1 / 1000 of the wavelength of the central operating frequency.

[0129] The feeding methods for microstrip antennas include direct feeding methods such as back-coaxial feeding and coplanar feeding, and electromagnetic coupling feeding methods such as slot coupling feeding and proximity coupling feeding. The rear coaxial feed can feed power from the rear of the antenna to the radiation conductor plate 14 using a coaxial line or connector that passes through the ground conductor plate 16 and the dielectric substrate 12 . The coplanar feed can feed the radiating conductor plate 14 with a microstrip line (not shown) disposed on the same plane as the radiating conductor plate 14 .

[0130] In the slot coupling feed, another dielectric substrate (not shown) is provided sandwiching the ground conductor plate 16, and the radiating conductor plate 14 and the microstrip line are formed on separate dielectric substrates. The radiating conductor plate 14 is excited by electromagnetically coupling the radiating conductor plate 14 and the microstrip line through a slot opened in the ground conductor plate 16.

[0131] In proximity coupling power supply, the dielectric substrate 12 has a laminated structure, and a dielectric substrate on which the radiating conductor plate 14 is formed is laminated with a dielectric substrate on which the strip conductor of the microstrip line and the ground conductor plate 16 are arranged.The strip conductor of the microstrip line is extended to the bottom of the radiating conductor plate 14, and the radiating conductor plate 14 and the microstrip line are electromagnetically coupled, thereby exciting the radiating conductor plate 14. 2(a) and (b) show another embodiment of the microstrip antenna. Note that the same components as those in FIG. 1 are given the same reference numerals and the description will be omitted as appropriate.

[0132] 2(a), the microstrip antenna 20 includes a dielectric substrate 22, a radiating conductor plate 14 provided on one surface of the dielectric substrate 22, a ground conductor plate 16 provided on the other surface of the dielectric substrate 22, and a high dielectric substrate (high dielectric) 24 disposed opposite the radiating conductor plate 14. The dielectric substrate 22 and the radiating conductor plate 14 can be configured to be spaced a predetermined distance from the high dielectric substrate 24 via a spacer 26. The dielectric substrate 22 is made of a substrate having a low dielectric constant, such as a Teflon substrate. The high dielectric substrate 24 is made of a dielectric material obtained by curing the above-mentioned resin composition. The gap between the dielectric substrate 22 and the high dielectric substrate 24 may be a space or may be filled with a dielectric material. Also, as shown in a microstrip antenna 20' in FIG. 2(b), a high dielectric substrate 24 may be abutted against the upper surface of the radiation conductor plate 14. In the microstrip antenna 20' shown in FIG.

[0133] <Dielectric Waveguide> In this embodiment, the dielectric waveguide includes a dielectric obtained by curing the resin composition of this embodiment and a conductor film covering the surface of the dielectric. The dielectric waveguide confines and transmits electromagnetic waves in a dielectric (dielectric medium). The conductive film can be made of a metal such as copper, or an oxide high-temperature superconductor.

[0134] <Electromagnetic wave absorber> In this embodiment, the electromagnetic wave absorber has a structure in which a support, a resistive film, a dielectric layer, and a reflective layer are laminated together. The electromagnetic wave absorber can be used as a λ / 4 type electromagnetic wave absorber having high electromagnetic wave absorbing performance.

[0135] The support may be a resin substrate, etc. The support can protect the resistive film and enhance the durability of the radio wave absorber. Examples of the resistive film include indium tin oxide and molybdenum-containing resistive films. The dielectric layer is formed by curing the resin composition of the present embodiment, and has a thickness of about 10 μm or more and 2000 μm or less. The reflective layer can function as a layer that reflects radio waves, and is, for example, a metal film.

[0136] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted as long as they do not impair the effects of the present invention. EXAMPLES

[0137] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0138] (Examples 1 to 2, Comparative Example 1) The following raw materials were mixed in the amounts shown in Table 1 at room temperature using a mixer, and then roll-kneaded at 70 to 100° C. The kneaded product was then cooled and pulverized to obtain a granular resin composition. The resin composition was then tableted under high pressure to obtain a tablet-shaped resin composition.

[0139] (High dielectric constant filler) High dielectric constant filler 1: Magnesium titanate (average particle size 0.8 μm)

[0140] High dielectric constant filler 2: Calcium titanate surface-treated with vinylsilane (Preparation method) 850 parts by weight of calcium titanate (average particle size 3 μm) and 5 parts by weight of vinyltriethoxysilane were mixed uniformly in a super mixer, then heat-treated at 120° C. for 8 hours and passed through a sieve with 100 μm openings to obtain high dielectric constant filler 2.

[0141] High dielectric constant filler 3: Calcium titanate surface-treated with phenylaminosilane (Preparation method) 850 parts by weight of calcium titanate (average particle size 3 μm) and 5 parts by weight of N-phenyl-γ-amino-propyltrimethoxysilane were mixed uniformly in a super mixer, then heat-treated at 120° C. for 8 hours and passed through a sieve with 100 μm openings to obtain high dielectric constant filler 3. High dielectric constant filler 4: Calcium titanate (average particle size 3 μm)

[0142] (Coupling Agent) Phenylaminosilane: Product name CF-4083 (N-phenyl-3-aminopropyltrimethoxysilane, manufactured by Dow Corning Toray Co., Ltd.)

[0143] (thermosetting resin) Epoxy resin: Phenol aralkyl type epoxy resin containing biphenylene skeleton (NC3000L, manufactured by Nippon Kayaku Co., Ltd.)

[0144] (hardening agent) Active ester hardener: Active ester hardener prepared according to the following method: (Method for preparing active ester curing agent) In a flask equipped with a thermometer, a dropping funnel, a cooling tube, a fractionating tube, and a stirrer, 203.0 g of 1,3-benzenedicarboxylic acid dichloride (molar number of acid chloride groups: 2.0 mol) and 1338 g of toluene were charged, and the inside of the system was reduced pressure and replaced with nitrogen to dissolve. Next, 96.5 g (0.67 mol) of α-naphthol and 219.5 g of dicyclopentadiene phenol resin (molar number of phenolic hydroxyl groups: 1.33 mol) were charged, and the inside of the system was reduced pressure and replaced with nitrogen to dissolve. Thereafter, while applying nitrogen gas purge, the inside of the system was controlled to 60°C or less, and 400 g of 20% aqueous sodium hydroxide solution was dropped over 3 hours. Then, stirring was continued under these conditions for 1.0 hour. After the reaction was completed, the mixture was left to stand and separated, and the aqueous layer was removed. Furthermore, water was added to the toluene phase in which the reactants were dissolved, and the mixture was stirred and mixed for about 15 minutes, and the aqueous layer was left to stand and separated to remove. This operation was repeated until the pH of the aqueous layer reached 7. Thereafter, water was removed by decanting to obtain an active ester resin in a toluene solution state with a non-volatile content of 65%. When the structure of the obtained active ester resin was confirmed, it was found to be R 1 and R 3 The structure had a hydrogen atom, Z a naphthyl group, and l 0. The average value k of the repeating units of the active ester resin was in the range of 0.5 to 1.0, calculated from the reaction equivalent ratio. The obtained active ester resin specifically had a structure represented by the following chemical formula. In the following formula, the average value k of the repeating units was 0.5 to 1.0.

[0145] [ka]

[0146] (catalyst) Catalyst 1: Tetraphenylphosphonium-4,4'-sulfonyldiphenolate Catalyst 2: Tetraphenylphosphonium bis(naphthalene-2,3-dioxy)phenylsilicate

[0147] (Release agent) Wax: Carnauba wax (TOWAX-132, manufactured by Toa Gosei Co., Ltd.) (Coloring agent) Black titanium oxide (Ako Kasei Co., Ltd.)

[0148] (Evaluation of dielectric constant and dielectric loss tangent using the cavity resonator method) First, a test piece was obtained using the resin composition. Specifically, the resin compositions prepared in the examples and comparative examples were applied to a Si substrate and prebaked at 120° C. for 4 minutes to form a resin film having a coating thickness of 12 μm. This was heated in an oven at 200°C for 90 minutes in a nitrogen atmosphere and subjected to hydrofluoric acid treatment (immersed in a 2 mass% hydrofluoric acid aqueous solution). After removing the substrate from the hydrofluoric acid, the cured film was peeled off from the Si substrate to prepare a test piece. The measurement equipment used was a network analyzer HP8510C, a synthesized sweeper HP83651A, and a test set HP8517B (all manufactured by Agilent Technologies). These equipment and a cylindrical cavity resonator (inner diameter φ42 mm, height 30 mm) were set up. The resonant frequency, 3 dB bandwidth, and transmitted power ratio were measured at frequencies of 1 GHz, 5 GHz, and 10 GHz with and without a test piece inserted in the resonator. The dielectric properties of the dielectric constant (Dk) and dielectric loss tangent (Df) were calculated analytically using software based on these measurement results. The measurement mode was TE. 011 Mode.

[0149] (Spiral flow measurement) Using a low-pressure transfer molding machine ("KTS-15" manufactured by Kotaki Seiki Co., Ltd.), the resin compositions obtained in the examples and comparative examples were injected into a mold for spiral flow measurement conforming to EMMI-1-66 under conditions of a mold temperature of 175°C, an injection pressure of 6.9 MPa, and a curing time of 180 seconds, and the flow length was measured.

[0150] (glass transition temperature, linear expansion coefficient) Using a transfer molding machine (KOTAKISEIKI Co., Ltd., "KTS-15"), the resin compositions obtained in each of the Examples and Comparative Examples were injected and molded at a mold temperature of 175°C, injection pressure of 9.8MPa, and curing time of 180 seconds to obtain test pieces (cured products) with long sides of 15mm, short sides of 4mm, and thickness of 4mm. The test pieces were post-cured at 175°C for 4 hours, and then measured using a thermomechanical analyzer in compression mode under the conditions of a measurement temperature range of 0°C to 320°C and a heating rate of 5°C / min. From the measurement results, the glass transition temperature (Tg) and the average linear expansion coefficient from 40°C to 80°C were calculated and designated as CTE1, and the average linear expansion coefficient from 190°C to 230°C was designated as CTE2.

[0151] (Evaluation of mechanical strength (flexural strength / flexural modulus)) The resin compositions obtained in each of the Examples and Comparative Examples were injected and molded into a mold using a low-pressure transfer molding machine ("KTS-30" manufactured by Kotaki Seiki Co., Ltd.) under conditions of a mold temperature of 175°C, an injection pressure of 9.8 MPa, and a curing time of 180 seconds. This resulted in a molded product having a width of 10 mm, a thickness of 4 mm, and a length of 80 mm. The molded product thus obtained was then post-cured at 175°C for 4 hours. This resulted in the preparation of test pieces for evaluation of mechanical strength. The flexural strength (N / mm) of the test pieces at room temperature (25°C) or 260°C was measured. 2 ) and flexural modulus (N / mm 2 ) was measured in accordance with JIS K 6911 at a head speed of 5 mm / min.

[0152] [Table 1]

[0153] As shown in Table 1, compared to the comparative example using non-surface-treated calcium titanate particles, the resin composition of the examples according to the present invention contained surface-treated calcium titanate particles, and thus a dielectric substrate was obtained that maintained a high dielectric constant, had a low dielectric tangent in the high frequency band, and also had excellent mechanical strength such as bending strength and bending modulus. It was presumed that a microstrip antenna equipped with a dielectric substrate obtained by curing the resin composition would enable higher frequencies, thus shortening the circuit and miniaturizing communication devices. It was also presumed that the desired effects would be obtained in a dielectric waveguide or electromagnetic wave absorber equipped with a dielectric (layer) obtained by curing the resin composition. [Explanation of symbols]

[0154] 10 Microstrip Antenna 12 Dielectric substrate 14 Radiating conductor plate 16 Grounding plate 20, 20' Microstrip Antenna 22 Dielectric Substrate 24 High dielectric substrate 26 Spacer a Cavity

Claims

1. A resin composition comprising at least one selected from calcium titanate particles and magnesium titanate particles, the particles being surface-treated with a silane compound.

2. The resin composition according to claim 1 , wherein the silane compound is a silane coupling agent.

3. The resin composition according to claim 2 , wherein the silane coupling agent is a phenylaminosilane or a vinylsilane.

4. The resin composition according to claim 1 , further comprising a thermosetting resin.

5. Further comprising a hardener, The resin composition of claim 1 , wherein the curing agent comprises an active ester curing agent.

6. The resin composition according to claim 1 , further comprising a curing catalyst.

7. The cured product of the resin composition has a flexural modulus of 300 N / mm at 260°C. 2 The resin composition according to claim 1, wherein:

8. The resin composition according to claim 1 , which is used as a material for forming a microstrip antenna.

9. The resin composition according to claim 1 , which is used as a material for forming a dielectric waveguide.

10. The resin composition according to claim 1 , which is used as a material for forming an electromagnetic wave absorber.

11. A dielectric substrate obtained by curing the resin composition according to any one of claims 1 to 7.

12. A dielectric substrate according to claim 11; a radiating conductor plate provided on one surface of the dielectric substrate; a ground conductor plate provided on the other surface of the dielectric substrate; A microstrip antenna comprising:

13. A dielectric substrate; a radiating conductor plate provided on one surface of the dielectric substrate; a ground conductor plate provided on the other surface of the dielectric substrate; a high dielectric material disposed opposite the radiation conductor plate; A microstrip antenna comprising: A microstrip antenna, wherein the high dielectric is constituted by the dielectric substrate according to claim 11.

Citation Information

Patent Citations

  • Resin composition and its use

    JP2004315653A

  • Antenna and electronic device including the same

    JP2018041998A

  • Resin composition

    JP2020105523A

  • Molding resin composition and electronic component device

    JP6870778B1